NF-κB RelA regulates temporal oligodendrocyte differentiation in the postnatal brains - Sompub, Kamonrapat; Bizen, Norihisa; Baldwin, Albert S.; Takebayashi, Hirohide (Frontiers in Cellular Neuroscience, 2025)
The NF-κB signaling pathway responds to a diverse range of cytokines and extracellular stresses, regulating immune responses, inflammation, cell proliferation, and cell death. However, the requirement of NF-κB in oligodendrocyte development and differentiation remains debatable. In this study, we generated conditional knockout mice of the RelA gene in the oligodendrocyte-lineage cells, which encodes a major subunit of NF-κB, and assessed its impact on oligodendrocyte differentiation. In RelA cKO mice, we observed a transient delay of oligodendrocyte differentiation in the postnatal cerebral cortex, albeit in a spatially and temporally restricted manner. Similarly, in the primary cultured oligodendrocyte differentiation model, the loss of RelA resulted in impaired terminal differentiation. Transcriptome analysis revealed a significant downregulation of numerous oligodendrocyte-related genes, including predicted NF-κB target genes. Furthermore, a comprehensive splicing analysis identified aberrant alternative splicing of Plp1, a most abundant and key gene involved in myelin sheath formation. These findings suggest that NF-κB/RelA contributes to the temporal and special control of oligodendrocyte development and differentiation in the postnatal brains. Our results highlight a previously underappreciated role of NF-κB in oligodendrocyte biology and encourage a re-evaluation of its physiological significance in the glial lineage.